Effect of foliar and substrate fertilization on lady palm seedling growth and development - da Luz, Petterson Baptista [UNESP]; de Oliveira Paiva, Patricia Duarte; Tavares, Armando Reis (Taylor & Francis Inc, 2008)
Lady palm, [Rhapis excelsa (Thunberg) Henry ex. Rehder] is one of the most cultivated ornamental palms in the world, for use as a vase plant or in shaded landscapes. Because limited information exists on lady palm response to fertilizers, the objective of this study was to evaluate the effect of different types of fertilization and substrates on lady palm seedling growth and development. Three year old lady palms were planted in 8-L pots, filled with a mix of soil, manure, and sand 1:1:1 (v:v:v), placed under a 50% shade, and irrigated with microspray. Treatments were substrate fertilization with 500 g P(2)O(5) and 100 g K(2)O per m(3); fertilization with 1.8 kg of P(2)O(5) (simple superphosphate) per m3; 50 g of nitrogen (N), P(2)O(5), and K(2)O of a granulated fertilizer (10:10:10) per m(3), control (without fertilization), and a foliar fertilization in addition to these treatments using the commercial product Biofert (8:9:9). Treatments were replicated four times in a randomized block design. Each treatment plot consisted of four plants. Data were collected at 140, 170, 200, 230, 260, and 290 days after transplanting (DAT) for plant heights, stem diameter at substrate level, number of leaves, shoots, and canopy, roots fresh and dry matter samples were harvest at 290 days. Foliar fertilization resulted in significantly greater plant height in a 140, 120, 200, and 230 DAT and plant diameter on the 140, 260, and 290 DAT. There was interaction among factors for number of leaves with fertilization based on P(2)O(5) and K(2)O when leaf fertilizer was added that resulted in a greater number of leaves.
Keywords: Rhapis; seedling production; fertilizers; palm tree